Among Indian rajahs and ryots - "Fraser, Andrew H. L." (Allahabad, 1975)
AMONG INDIAN RAJAHS AND RYOTS A Civil Servant's Recollections amp Impressions Of Thirty-Seven Years Of Work amp Sport In The Central Provinces amp Bengal By Sir Andrew H.L.Fraser CONTENTS: EARLY DAYS EUROPEAN OFFICERS OF MY PROVINCE MORE ABOUT CENTRAL PROVINCES OFFICERS INDIAN OFFICER OR MY PROVINCE JUDICIAL AND EXECUTIVE FUNCTIONS OF OUR OFFICERS SOME INDIAN FRIENDS THE INDIAN PEOPLES INDIAN LADIES GRAIN RIOTS IN THE NAGPUH DISTRICT THE KHOND RISING IN THE KALAHANDI
Keywords: "Fraser, Andrew H.L Biography"